Life estimation and analysis of dielectric strength, hydrocarbon backbone and oxidation of high voltage multi stressed EPDM composites. (1st February 2018) - Khattak, Abraiz; Amin, Muhammad; Iqbal, Muhammad; Abbas, Naveed
Abstract: Micro and nanocomposites of ethylene propylene diene monomer (EPDM) are recently studied for different characteristics. Study on life estimation and effects of multiple stresses on its dielectric strength and backbone scission and oxidation is also vital for endorsement of these composites for high voltage insulation and other outdoor applications. In order to achieve these goals, unfilled EPDM and its micro and nanocomposites are prepared at 23 phr micro silica and 6 phr nanosilica loadings respectively. Prepared samples are energized at 2.5 kV AC voltage and subjected for a long time to heat, ultraviolet radiation, acid rain, humidity and salt fog in accelerated manner in laboratory. Dielectric strength, leakage current and intensity of saturated backbone and carbonyl group are periodically measured. Loss in dielectric strength, increase in leakage current and backbone degradation and oxidation were observed in all samples. These effects were least in the case of EPDM nanocomposite. The nanocomposite sample also demonstrated longest shelf life.